First-Line Treatment of Metastatic Pancreatic Cancer - Tokh, Mohammed; Bathini, Venu; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2012)
Metastatic pancreatic cancer is an aggressive malignancy that is difficult to treat. Gemcitabine monotherapy has been used first line and many contemporary treatment approaches have focused on gemcitabine plus experimental agents. The 2012 ASCO Gastrointestinal Cancers Symposium Abstract #213 is a study of gemcitabine with IPI-926, a novel hedgehog pathway inhibitor. Abstract #227 is a study of gemcitabine with 90Y-hPAM4 radioimmunotherapy with yttrium labeled anti-mucin humanized antibody. Abstract #296 is a study of gemcitabine with temsirolimus, an mTOR inhibitor. Gemcitabine and erlotinib has shown slight advantages to gemcitabine alone. Abstract #253 takes this one step further and evaluates gemcitabine and erlotinib with apricoxib, a COX-2 inhibitor. FOLFIRINOX has shown superiority to gemcitabine; however, doing so at the cost of significantly greater toxicity. Abstract #199, is a study which examines the cost effectiveness of first line FOLFIRINOX approaches. Another cost effective study is portrayed in Abstract #372, a study evaluating the survival of unresectable pancreatic cancer patients treated with gemcitabine and the disease course is followed clinically without radiographic follow-up.